Algebraische Zahlentheorie: 2. bis 8. August 1992 - Frey, Gerhard; Leopoldt, Heinrich-Wolfgang; Roquette, Peter (Tagungsbericht, 1992)
Graham R. Everest; Albrecht Fröhlich; Erich Lamprecht; Jürgen Neukirch; Jannis A. Antoniadis; Werner Bauer; Eva Bayer-Fluckiger; Sigrid Böge; Harry Cohn; Salvador Comalada; Christopher Deninger; Matthias Flach; Gerhard Frey; Wulf-Dieter Geyer; Barry William Green; Franz Halter-Koch; Moshe Jarden; Wolfram Jehne; Ernst Kani; Ian Kiming; Guido Kings; Ernst Kleinert; Norbert Klingen; Helmut Koch; Bernhard Köck; Johann B. Leicht; Heinrich-Wolfg. Leopoldt; Armin Leutbecher; Falko Lorenz; Manohar L. Madan; Gunter Malle; B. Heinrich Matzat; Jean-Francois Mestre; Tauno Metsaenkylae; Katsuya Miyake; Enric Nart; Robert W. K. Odoni; Hans Opolka; Florian Pop; Hans-Peter Rehm; Jürgen Ritter; Peter Roquette; Hans-Georg Rück; Reinhard Schertz; Alexander Schmidt; Claus-Günther Schmidt; Rene Schoof; Vladimir A. Smirnov; Michael Spieß; Martin J. Taylor; Annette Werner; Kay Wingberg; Ernst-Wilhelm Zink